Determinants of self-employment among Polish and Romanian immigrants in Germany. Issue 4 (3rd July 2016) - Szarucki, Marek; Brzozowski, Jan; Stankevičienė, Jelena
Abstract: This empirical study investigates the determinants of self-employment propensity of Polish and Romanian immigrants in Germany. The German economy is an important object of analysis, as it is the most important destination for international migrants in the European Union. In the paper, we use the recently collected M sample of the German Socio-Economic Panel to examine which personal, country of birth-specific socio-economic and cultural factors influence the self-employment propensity of immigrants. The results of binominal logit regression show that the Central European migrants exhibit different self-employment propensity than migrants from former Yugoslavia, Russian and Kazakhstan, Turkey and Italy, with the self-employment aversion especially strong among Romanians. These differences remain substantial even after controlling for social and human capital endowment of the individuals. This study offers important policy recommendations, showing the potential obstacles in encouraging entrepreneurial activity of immigrants. This topic is becoming increasingly important with the current migration crisis in the EU, caused by intensive inflow of asylum-seeking foreigners in 2015.